ANALISIS FAKTOR MOTIVASI TERHADAP EFEKTIVITAS ORGANISASI PADA KARYAWAN MEDICAL REPRESENTATIF AREA MALANG - Nurul Hidayatin Nisa'; Masreviastuti Masreviastuti; Ayu Febriyanti Puspitasari (Universitas Muhammadiyah Gresik, 2021)
Organizational effectiveness is an issue that is being considered by many organizations, organizational effectiveness can be a reference for whether the organization has succeeded in achieving its planned goals or objectives. Several factors affect the effectiveness of the organization, one of which is the motivational factors of the members of the organization. According to research from K.P. Singh (2017) the dominant motivational factors for organizational effectiveness are: recognition and empowerment. This study was conducted on medical representative employees who are the spearhead of pharmaceutical companies. It is known that medical representatives have a significant role in the company, so the company is expected to pay attention to the factors that affect employee motivation so that employee effectiveness is formed. This study includes a quantitative method of explanatory research using a questionnaire questionnaire to medical representative employees. The data analysis technique used is multiple linear regression analysis. The results of this study indicate that the motivational factors, namely recognition and empowerment, have a dominant influence on organizational effectiveness and partially or jointly have a significant effect on organizational effectiveness.